NORTHERN IRISH ADOLESCENTS’ ATTITUDES TOWARDS LEARNING A FOREIGN LANGUAGE: WHAT CAN WE LEARN FROM THEM? - Udi Samanhudi (Universitas Bengkulu, 2019)
Over the last few decades, scholars concerned with language and education have studied the relationship between adolescents’ attitudes and foreign language learning. This topic has been an important area of study in the field of applied linguistics predominantly from a psychological perspective. This research used secondary data from the Young Life and Times (YLT) and employed a descriptive qualitative research with a cross-sectional design. The Chi-Square test was used in order to test the five hypotheses proposed in this study. This present study found that gender and residential locations were significant factors relating to the 16-year old adolescents’ attitudes toward learning a foreign language. Conversely, this study found that there was no statistically significant evidence of differences among the other three variables (the family affluence, school types attended and religions) in relation to the young people’s attitudes to the foreign language. This finding may be useful as a reflection of how the current modern language learning policy is implemented and how teenagers, especially in the context of Northern Ireland, respond to the policy.Keywords: Adolescents’ Attitudes, Learning, foreign language learning